Normative Analysis of Online Registration of Sound Trademarks in Indonesia - Hanifah Is'aad; Andry Setiawan (Law Research Review Quarterly, 2026)
The development of non-traditional brands has led to the expansion of trademark legal protection, including against sound brands. In Indonesia, voice trademarks have been recognized normatively in Law Number 20 of 2016 concerning Trademarks and Geographical Indications and are registered through an online trademark registration system managed by the Directorate General of Intellectual Property. However, this recognition raises various legal and institutional issues, especially related to legal certainty, technical standards for registration, and the effectiveness of the online registration mechanism. This study aims to analyze the normative regulation of voice trademark registration in the Indonesian legal system and examine the legal implications of online voice trademark registration. This study uses a normative legal research method with a legislative approach and a comparative legal approach, by comparing the regulation and practice of voting trademark registration in Indonesia, Australia, and the European Union. In addition, a conceptual approach is used to examine the concept of non-traditional brands, differentiating power, and legal certainty. The results show that although sound trademarks have been normatively recognized, the trademark registration system in Indonesia has not been supported by adequate technical arrangements and operational standards. The absence of examination guidelines and limited transparency in the online registration system create legal uncertainty and expand the administrative discretion of the examiner. This condition has an impact on weak legal protection for applicants and interested parties. This study concludes that strengthening implementing and institutional regulations is needed to realize effective, transparent, and fair registration of voice trademarks.